Anti- Anopheles darlingi saliva antibodies as marker of Plasmodium vivax infection and clinical immunity in the Brazilian Amazon - Tadei Wanderli; Camargo Luís; Reis-Filho Antonio; Rocha Bruno; Andrade Bruno; Moreira Luciano; Barral Aldina; Barral-Netto Manoel (Malaria Journal, 2009)
Abstract Background Despite governmental and private efforts on providing malaria control, this disease continues to be a major health threat. Thus, innovative strategies are needed to reduce disease burden. The malaria vectors, through the injection of saliva into the host skin, play important role on disease transmission and may influence malaria morbidity. This study describes the humoral immune response against Anopheles (An.) darlingi saliva in volunteers from the Brazilian Amazon and addresses the association between levels of specific antibodies and clinical presentation of Plasmodium (P.) vivax infection. Methods Adult volunteers from communities in the Rondônia State, Brazil, were screened in order to assess the presence of P. vivax infection by light microscopy and nested PCR. Non-infected volunteers and individuals with symptomatic or symptomless infection were randomly selected and plasma collected. An. darlingi salivary gland sonicates (SGS) were prepared and used to measure anti-saliva antibody levels. Plasma interleukin (IL)-10 and interferon (IFN)-γ levels were also estimated and correlated to anti-SGS levels. Results Individuals infected with P. vivax presented higher levels of anti-SGS than non-infected individuals and antibody levels could discriminate infection. Furthermore, anti-saliva antibody measurement was also useful to distinguish asymptomatic infection from non-infection, with a high likelihood ratio. Interestingly, individuals with asymptomatic parasitaemia presented higher titers of anti-SGS and lower IFN-γ/IL-10 ratio than symptomatic ones. In P. vivax -infected asymptomatic individuals, the IFN-γ/IL-10 ratio was inversely correlated to anti-SGS titers, although not for while in symptomatic volunteers. Conclusion The estimation of anti- An. darlingi antibody levels can indicate the probable P. vivax infection status and also could serve as a marker of disease severity in this region of Brazilian Amazon.